Willingness to Pay for Destination Quality Improvement: Case Study of Baru Beach, Yogyakarta - Setiawan, Ferry; Saptutyningsih, Endah (Universitas Muhammadiyah Yogyakarta, 2022)
This study aims to analyze the willingness to pay visitors for the quality improvement of Baru Beach. The respondents of this research are visitors in Baru Beach. This study uses the contingent valuation method (CVM). Accidental techniques were used to collect data from 150 tourists in Baru Beach. This paper found that the average value of willingness to pay (WTP) is IDR15,000 obtained using dichotomous choice. In addition, variables of age, income, education level, frequency of visits, and visitor perceptions were positive to WTP. Distance and marital status have no significant effect.